INNOVATIVE SOCIAL MEDIA MARKETING: TRANSFORMING B2B SME PERFORMANCE THROUGH PRODUCT INNOVATION - Farida, Ida; Siagian, Yolanda Masnita (EBID: Ekonomi Bisnis Digital, 2024)
The development of firm performance in the B2B sector is increasingly complex in the digital era, influenced by globalization, digitalization, and socio-economic changes. This study aims to explore the impact of social media marketing (SMM) on firm performance, with product innovation as a mediating variable. A quantitative research approach was employed, analyzing data from various B2B companies. The results indicate that the use of SMM, both internally and externally, positively contributes to firm performance, particularly through product innovation. The study also finds that the impact of SMM usage varies depending on the type of marketing innovation implemented. These findings provide new insights into the relationship between social media and firm performance in B2B contexts and reinforce existing theories regarding the importance of product innovation in enhancing firm performance. This research is expected to serve as an important reference for companies in developing marketing strategies in the digital era.